EBV Positive Diffuse Large B Cell Lymphoma and Chronic Lymphocytic Leukemia Patients Exhibit Increased Anti-dUTPase Antibodies - Williams, Marshall (Cancers (Basel), 2018)
The Epstein-Barr virus (EBV), which is a ubiquitous γ-herpesvirus, establishes a latent infection in more than 90% of the global adult population. EBV-associated malignancies have increased by 14.6% over the last 20 years, and account for approximately 1.5% of all cancers worldwide and 1.8% of all cancer deaths. However, the potential involvement/contribution of lytic proteins to the pathophysiology of EBV-associated cancers is not well understood. We have previously demonstrated that the EBV-deoxyuridine triphosphate nucleotidohydrolase (dUTPase) modulates innate and adaptive immune responses by engaging the Toll-Like Receptor 2 (TLR2), which leads to the modulation of downstream genes involved in oncogenesis, chronic inflammation, and in effector T-cell function. Furthermore, examination of serum samples from diffuse large B-cell lymphoma (DLBCL) and chronic lymphocytic leukemia patients revealed the presence of increased levels of anti-dUTPase antibodies in both cohorts compared to controls with the highest levels (3.67-fold increase) observed in DLBCL female cases and the lowest (2.12-fold increase) in DLBCL males. Using computer-generated algorithms, dUTPase amino acid sequence alignments, and functional studies of BLLF3 mutants, we identified a putative amino acid motif involved with TLR2 interaction. These findings suggest that the EBV-dUTPase: TLR2 interaction is a potential molecular target that could be used for developing novel therapeutics (small molecules/vaccines).